Effects of Site Directed Mutagenesis of the Second Exon of the Adenovirus 5 E1A Gene on Transcriptional Activation - Skiadopoulos, Mario (My University, 1988)
The early region 1a oncogene of adenovirus 5 codes for proteins that can activate transcription of viral and cellular genes. This study describes the construction of three deletions and one point mutation that together span the entire coding region of the second exon of E1A. The exon-2 mutants were tested for their ability to activate transcription from the adenovirus early region 3 promoter (E3) in transient expression assays. Dl1116 (dl aa 205-221) did not affect transactivation of E3 in pKCAT-23. Sub1117 (dl exon-2 aa) and dl1115 (dl aa 188-204) were unable to activate transcription. Pm1131 (SER-219 to stop) had a reduced transactivating efficiency but was still able to stimulate transcription. These results define the 3' boundary of a transactivation domain on the E1A proteins as being between positions 188 and 204. Results obtained in our lab define the 5' boundary as being between 138-147 (Jelsma et al., 1988). The mutants that could not transactivate were tested for their ability to block wildtype E1A transactivation of the E3 promoter in assays similar to those described by Glenn and Ricciardi (1987). Dl1115 and sub1117 appeared to block transactivation by WT E1A. In transient expression assays, the fatty acid sodium butyrate was found to stimulate transcription of the CAT gene, when added to the medium of HeLa cells transfected with pKCAT-23. This suggests that sodium butyrate is transactivating the Ad 5 E3 promoter.
Mutagenesis of the Second Exon of the AD5 E1A Gene
Keywords: mutagenesis; exon; AD5; adenovirus 5; transciption; activate; gene